Synthesis of New Enamines and Its Microbial Activity - Utale, P.S.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
2-Hydroxy substituted acetophenone condensed with dimethylamine and diphenyl amine in ethanol medium in presences of cone.H2SO4 affords enamines. These compounds are tested against testorganisms Staphylococcus aureus, Streptoccous pyogenes, S.agalacriae, S. facecalis, Corynebacterium ulcerans, C.minuttissimum. Clostridium septicum, Clostridium tetari andEscherichia coli.